Perbandingan Efficientnet, Visual Geometry Group 16, dan Residual Network 50 Untuk Klasifikasi Kendaraan Bermotor - Andrianto, Andrianto; Tahyudin, Imam; Karyono, Giat (Forum Kerjasama Pendidikan Tinggi, 2024)
This study compares the performance of three Convolutional Neural Network (CNN) models—EfficientNet, VGG16, and ResNet50—in motor vehicle classification tasks using the